Máquinas paradas e pés à obra: futebol e lazer fabril em fortaleza (1949-1965) - Martins, Pedro Paulo da Silva (2017)
Through leisure and sportive practices, one could grasp several social and cultural meanings in a given society. This assumption is also valid in historical studies about labour world, once this can be studied beyond production relations. This research aims to study the football club Usina Ceará Atlético Clube – squad initially consisted only by workers from Siqueira Gurgel factory, that was placed at Otávio Bonfim neighborhood and worked mainly processing cotton and oils. Through this we have as a goal perceive how the football practice that started at the factory happened and how this affects workers life. The temporal framing of our study comprise the years between 1949 and 1965, existing period of the researched club. Flowing alongside the main goal, this study aims to examine how leisure equipments built by Siqueira Gurgel were institutionalized areas of leisure distinction between its visitors, how the professionalization process happened to football clubs members of Federação Cearense de Desportos (FCD), and to analyze the football practice developed at the inter-factory circuit under Serviço Social da Indústria (SESI) supervision.